The Contours of African Identity: Culture, Diaspora, and Indigenous Knowledge - (:unkn) unknown (My University, 2025)
Culture is a subject dear to my heart. Africa is not just an identity; it is also a destiny, a moral obligation. The culture of each ethnic group holds together the authentic social and metaphysical fabric of traditional practices, oral literature, music, art, and rites through which identities are built. African culture is varied and manifold, consisting of various ethnic groups, with each possessing unique characteristics. This paper explores some of the focal areas of ‘Africanness’ and my position as an “African’. This study aims to critically explore the essence of Africa and African culture by interrogating the historical and contemporary constructions of black identity within both the African continent and the African Diaspora. The study also seeks to examine how colonial domination, imaginative narratives, and interpretive frameworks have shaped political and theoretical understandings of race, culture, and identity. The study also investigates the ongoing relevance of African cultural expressions and identities within Africa itself, questioning how these concepts function, evolve, and resist in the face of internal and external influences. A contextual approach was employed in this study. The primary source for data collection was oral interviews. The participants were selected for interviews in relation to their informative qualities and their dedication, commitment and determination to Local Knowledge and Indigenous Knowledge Systems. Thirteen participants were interviewed for this study, comprising seven (7) traditional music practitioners, two (2) traditional poets, two (2) creative practitioners and two (2) Anthropologists. It has emerged from this study that in terms of African identity, establishing and fully owning identity is important for political, economic, and social progression. Oral accounts and literary evidence have also shown that oral tradition is very important in African culture, as it ensures the passage of cultur
Keywords: African Research